Association of the lipoprotein lipase gene Ser447Ter polymorphism with hypertension and blood pressure variation: evidence from an updated meta-analysis. (3rd October 2017) - Wang, June; Du, Shenlin; Wang, Jiamin; Zhu, Man; Wen, Xue; Yang, Weiqing
ABSTRACT: The polymorphism of lipoprotein lipase (LPL) gene Ser447Ter (S447X) has long been linked to hypertension and blood pressure variation, but the established data remained controversial. To better elucidate this inconsistency, a meta-analysis was conducted. We comprehensively searched electronic databases, including Pubmed, EMBASE, China National Knowledge Infrastructure (CNKI), Web of Science, for all literatures with the last update on February 2016. The strength of association was calculated by using odds ratios (ORs) and weighted mean differences (WMDs) with corresponding 95% confidence intervals (CIs). Further stratified analyses, cumulative meta-analysis analysis, and sensitivity analyses were performed. A total of 14 studies (3592 cases and 4643 controls) for hypertension and 14 studies ( n = 9254) for blood pressure were included. Overall, significant associations were revealed between S447X polymorphism and hypertension risk using allelic comparison (OR = 0.86, 95%CI 0.77 to 0.96), heterozygote comparison (OR = 0.85, 95%CI 0.75 to 0.96), and the dominant model (OR = 0.85, 95%CI 0.75 to 0.96), especially in Asians. Furthermore, in subgroup analyses restricted to the population-based controls studies, the high-quality studies, and the large sample size studies, these significant associations were still observed. As for blood pressure association, significant reductions of systolic blood pressure (WMD = −1.25 mmHg, 95%CI −2.25 to −0.25 mmHg) and diastolic blood pressure (WMD = −1.91 mmHg, 95%CI −3.25 to −0.56 mmHg) levels were found using dominant model. No publication bias was observed in any comparison model. Therefore, current meta-analysis suggested that the LPL S447X polymorphism is likely to be a protective factor in the development of hypertension.